Implementing flipped classroom using TED-ED - Marina O. Polukhina; Elvira E. Valleva (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Modern higher education is on the verge of change caused by the paradigm shift - the transition from classical to progressive. Nowadays, it is already impossible to imagine education without the use of information and communication technologies. Due to this, there is a need to reconsider methods and approaches to teaching in higher educational institutions. The concept of higher education should correlate with the requirements of the society that a graduate should satisfy. A graduate of the 21st century is a subject of his own activity, who possesses the necessary competences to become successful in the society. Consequently, a teacher faces the task of finding ways and means of integrating new formats of education into the learning process, thanks to which the student will be able to master the 21st century competences. In order to improve the quality of education, the authors introduce one of the components of the blended learning strategy - the Flipped Classroom. The paper presents the Flipped Classroom concept, the possibilities of implementing this technology using the educational platform TED-Ed which, in its turn, allows satisfying the modern requirements of integrating information technologies in the educational context. The authors have tried out this technology. The materials were created for the English Language class,intended for independent and classroom work of second-year students studying in the department of construction. Conclusions are made regarding the effectiveness of the approach. Thus, implementing the Flipped Classroom has allowed the authors to improve the results of learning in general, and students’ autonomous learning skills in particular. The authors consider the Flipped Classroom and the TED-Ed resource as a great advantage due to the possibility of using them in various fields of education.